ANALISIS KEMAMPUAN VEGETASI DALAM MEREDAM KEBISINGAN - Putra, Imam Syah; Rombang, J. A.; Nurmawan, W. (Universitas Sam Ratulangi, 2018)
ABSTRACTÂ Noise is one of the environmental problems that is often overlooked. To solve an environmental problems like this, vegetation is considered as the most effective and efficient noise damper. This research was conducted in Warembungan Village, Pineleng District, Minahasa Regency from May to July 2018, using the 3 factor factorial field experiment method in a Randomized Block Design, 3 main factors are vegetation canopy cover level, rotation per minute (RPM) rate of sound source, and distance level. The vegetation canopy cover level was determined purposively.The aim of this research to determine the capacity of various level of vegetation canopy coverage to reduce noise at various levels of noise. The role of vegetation in reducing noise depends on the coverage of vegetation canopy. At low level coverage of vegetation canopy, noise decreases about 1.25 dBA or 1.69% lower than the noise recorded without vegetation coverage. at the middle level coverage and high level coverage of vegetation canopy, the noises decrease aboutÂ 2.46 dBA (or 3.32% lower) and 5.72 dBA (or 7.82% lower) respectively. Keywords: sound, noise, vegetation, canopy cover